PENGARUH KUALITAS PELAYANAN, CITRA PERUSAHAAN DAN KEPERCAYAAN TERHADAP LOYALITAS NASABAH PT. BRI TBK CABANG GIANYAR - I Gede Nyoman Carlos W. Mada; Ratih Permata Dewi; Ni Kd Sioaji Yamawati (Faculty of Economics and Business, Universitas Warmadewa, 2022)
This study aims to analyze the effect of Service Quality, Corporate Image, and Trust on Customer Loyalty (Case Study on Customers of PT. Bank Rakyat Indonesia Tbk Gianyar Branch). PT. Bank Rakyat Indonesia Tbk as one of the largest banks with branches in every city and units in almost every sub-district level, has become one of the banks used as customers to make savings and loans and other transactions. The data used are primary data. Primary data obtained from questionnaires distributed to customers of PT. Bank Rakyat Indonesia Tbk Gianyar Branch. The data analysis technique used is multiple linear regression analysis. The results showed that Service Quality, Company Image, Trust Affect Customer Loyalty.